Strategi Memberikan Prompt Yang Efektif pada Chatgpt untuk Hasil Optimal - Sri Utami; R. Joko Musridho; Dina Meysi Chandra; Sarwo Dinata (Journal on Pustaka Cendekia Informatika, 2024)
The use of artificial intelligence such as ChatGPT is increasingly popular across various fields, including education, research, and creative industries. However, not all users obtain responses that align with their expectations. This article aims to examine strategies for providing effective prompts to ChatGPT to ensure that the generated output meets user needs. The method used in this study is a literature review, referring to various recent sources on prompt engineering techniques and best practices for interacting with generative language models. The results of this study indicate that word choice, sentence structure, and clear context in a prompt significantly affect the quality of responses produced by ChatGPT. This article also provides several examples of effective prompts as a guide for users to interact optimally with generative AI models.